THE EFFECTS OF THE VARIATION OF THE ELECTRODE AND ELECTROLYTE MATERIALS ON WATER HYDROLYSIS FOR HYDROGEN PRODUCTION - M. Isa; M.R. Islam; A.N.A.Yahaya; M.G Sumdani (Marine Frontier, 2021)
Water electrolysis is a simple and easy way to produce hydrogen though there are some major challenges about energy consumption, production and maintenance cost, and durability. This study presents an experimental analysis of hydrogen production by water electrolysis using different electrodes and electrolyte to find an effective way of hydrogen production. The purpose of this research work is to identify the best electrode and electrolyte materials for hydrogen production along with some effective operating parameters. Experiments were performed on a water electrolysis cell with three electrode materials (stainless steel, carbon steel (iron), galvanized zinc) and three electrolyte materials (Potassium hydroxide (KOH), Sodium hydroxide (????????????????), Sodium bicarbonate (NaHCO3)) alternatively. Throughout the experiments, different composition of electrodes, different composition of electrolytes, and ampere were investigated on volume of hydrogen production. Results showed that various factors have the influence on the performance of water electrolysis. Indeed, this study revealed that the hydrogen gas production efficiency of carbon steel-based electrode is the highest (146%) compared with other electrodes over the range of operating parameters tested. Among these three electrode, carbon steel can be the best selection for the maximum hydrogen production compared to other electrodes under the present experimental conditions.